2008
DOI: 10.1097/ccm.0b013e31818b9375
|View full text |Cite
|
Sign up to set email alerts
|

Timely selection of adequate antifungal therapy for candidemia in the critically ill: Donʼt let the yeast rise!*

Abstract: enth of the Barnes-Jewish cases of candidemia and the highest proportion that were inadequately treated (37.1%). As fluconazole is a relatively nontoxic agent, arguably all patients should commence on 12 mg/kg fluconazole (adjusted if renal failure is present) and the dosage reduced, if appropriate, once the species is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Concurrent with increasing numbers of invasive candidal infections, surveillance programmes have become important in defining the species distribution and antifungal resistance patterns of the responsible pathogens, and thus are providing the information necessary for appropriate empirical antifungal therapy [1][2][3][4][5][6]. Data from several sources show that mortality rates and resource utilisation increase significantly when empirical therapy is delayed or inadequate (wrong dose, resistant isolate), further underscoring the importance of detailed epidemiological data [1,4,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with increasing numbers of invasive candidal infections, surveillance programmes have become important in defining the species distribution and antifungal resistance patterns of the responsible pathogens, and thus are providing the information necessary for appropriate empirical antifungal therapy [1][2][3][4][5][6]. Data from several sources show that mortality rates and resource utilisation increase significantly when empirical therapy is delayed or inadequate (wrong dose, resistant isolate), further underscoring the importance of detailed epidemiological data [1,4,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…achieve suitable growth for MIC testing by 24 h of incubation (14)(15)(16)36). Given the facts that a shorter incubation period is more efficient and practical for use in the clinical laboratory (16,36) and that research has shown that early/ correct antifungal treatment has a positive effect on outcomes for patients with candidemia (5,6,12,19,20,23,27,29,33,53), the CLSI has determined that fluconazole MICs may be used after a 24-h incubation, providing earlier clinically useful information to clinicians caring for patients with invasive candidiasis (IC) (31,36). Currently, the CLSI recommends that MICs for the newer triazoles, posaconazole and voriconazole, be read after 48 h of incubation for testing of Candida spp.…”
mentioning
confidence: 99%
“…The clinical outcome in patients with invasive candidiasis largely depends on the timeliness in antifungal therapy (Hope et al, 2012;Ullmann et al, 2012). Many clinical investigations have clearly shown that delayed approach in antifungal therapy has a negative impact on survival Ahmed et al, 2014;Blot, Vandewoude, Hoste, & Colardyn, 2002;Corona, Cislaghi, & Singer, 2008;Elhoufi et al, 2014;Garey et al, 2006;Mardani et al, 2011;Morrell, Fraser, & Kollef, 2005;Skrobik & Laverdiere, 2013;Viaggi, Tascini, & Menichetti, 2014;Yildirmak, Gedik, Simsek, Iris, & Gucuyener, 2013). Based upon the diagnostic possibility of IFIs, various strategies including prophylaxis, empirical, preemptive, or targeted therapy may be pursued.…”
Section: Therapeutic Approaches Towards Invasive Candidiasismentioning
confidence: 99%